Upaya Meningkatkan Prestasi Siswa Pada Konsep Perubahan Benda Dengan Mengunakan Metode Demontrasi Siswa Kelas V SD Negeri 024 Rambah Tahun Pelajaran 2015/ 2016 - . Ermawati (STKIP Rokania Pasir Pangaraian, 2018)
Abstract, The purpose of this study conducted by the authors is to find out how much influence the model of learning by using the method of cooperative Demonstration on material changes in objects. It turns out to improve student learning outcomes from improvements in learning that is carried out. The subjects of the study were the fourth graders of SD Negeri 024 Rambah Semester I of Lesson 2016/20167. In following the lesson, the average of students' activity has increased significantly from cycle II, from 46.79% to 73.07%. After the evaluation is done at the end of cycle II obtained learning results with an average value of 78.84 and 94.87% completeness. This means that the completeness of the class has been achieved because it already meets the success indicator of 75%. Therefore there is no need to hold the next cycle